Ventilator-Associated Events: Prevalence, Outcome, and Relationship With Ventilator-Associated Pneumonia*. Issue 9 (September 2015) - Bouadma, Lila; Sonneville, Romain; Garrouste-Orgeas, Maité; Darmon, Michael; Souweine, Bertrand; Voiriot, Guillaume; Kallel, Hatem; Schwebel, Carole; Goldgran-Toledano, Dany; Dumenil, Anne-Sylvie; Argaud, Laurent; Ruckly, Stéphane; et al.
Abstract : Objectives: Centers for Disease Control and Prevention built up new surveillance paradigms for the patients on mechanical ventilation and the ventilator-associated events, comprising ventilator-associated conditions and infection-related ventilator-associated complications. We assess 1) the current epidemiology of ventilator-associated event, 2) the relationship between ventilator-associated event and ventilator-associated pneumonia, and 3) the impact of ventilator-associated event on antimicrobials consumption and mechanical ventilation duration. Design: Inception cohort study from the longitudinal prospective French multicenter OUTCOMEREA database (1996-2012). Patients: Patients on mechanical ventilation for greater than or equal to 5 consecutive days were classified as to the presence of a ventilator-associated event episode, using slightly modified Centers for Disease Control and Prevention definitions. Intervention: None. Measurements and Main Results: Among the 3, 028 patients, 2, 331 patients (77%) had at least one ventilator-associated condition, and 869 patients (29%) had one infection-related ventilator-associated complication episode. Multiple causes, or the lack of identified cause, were frequent. The leading causes associated with ventilator-associated condition and infection-related ventilator-associated complication were nosocomial infections (27.3% and 43.8%), including ventilator-associated pneumonia (14.5% and 27.6%). Sensitivity and specificity of diagnosing ventilator-associated pneumonia were 0.92 and 0.28 for ventilator-associated condition and 0.67 and 0.75 for infection-related ventilator-associated complication, respectively. A good correlation was observed between ventilator-associated condition and infection-related ventilator-associated complication episodes, and ventilator-associated pneumonia occurrence: R 2 = 0.69 and 0.82 ( p < 0.0001). The median number of days alive without antibiotics and mechanical ventilation at day 28 was significantly higher in patients without any ventilator-associated event ( p < 0.05). Ventilator-associated condition and infection-related ventilator-associated complication rates were closely correlated with antibiotic use within each ICU: R 2 = 0.987 and 0.99, respectively ( p < 0.0001). Conclusions: Ventilator-associated event is very common in a population at risk and more importantly highly related to antimicrobial consumption and may serve as surrogate quality indicator for improvement programs.